The Relationship between the Nature of Humanity and the Philosophy of Education - Siti Nurislamiah; Ariesta Setyawati; Hasim (IAIN KENDARI, 2026)
Human beings, as viewed through the lens of science, are highly dependent on the methodologies applied. Advocates of psychoanalytic theory assert that humans are homo volens (creatures with desires). According to this perspective, humans exhibit behaviors that result from the interaction of biological (id), psychological (ego), and social (superego) components. Within humans, there are elements of the animalistic (instinctive), rational (intellectual), and moral (values). Behaviorist theorists, on the other hand, label humans as homo mechanicus (mechanical beings). According to this approach, all human behaviors are shaped through the learning process from their environment, not determined by inherent aspects. Cognitive theorists refer to humans as homo sapiens (thinking beings). According to this perspective, humans are no longer seen as creatures passively reacting to their environment; rather, they are beings constantly engaged in thinking. Cognitive theorists criticize opinions that tend to consider the mind as unreal because it seems not to influence events. However, thinking, deciding, expressing, understanding, and the like are undeniable facts of human life. The Quran designates humans with three terms: al-basyar, an-nas, and al-ins or al-insan. These three terms are commonly interpreted as referring to humans, although, when examined linguistically and according to the Quran itself, each term carries distinct meanings.